Histopathology of Aculeastrum americanum on Rubus idaeus and insights into the chloroplast-pathogen interaction - Barbosa, Lucas Henrique Santos; Neumann, Ulla; Timmers, Ton; Andersen, Tonni Grube; Appezzato-da-Glória, Beatriz (Frontiers in Plant Science, 2025)
IntroductionRaspberry late leaf rust, caused by Aculeastrum americanum (Farl.) M. Scholler & U. Braun has been reported in several countries. All aerial parts of the plant can be infected, with the primary symptoms of this disease being powdery yellow spots. Lesions reduce leaf gas exchange and lead to early defoliation. Moreover, infected fruits become unmarketable, resulting in severe yield losses. Despite the growing threat of this rust, the histopathology of A. americanum on raspberry remains poorly understood, particularly on Rubus idaeus L., one of the widely cultivated and economically important raspberry species.MethodsThis study provides a detailed analysis of the infection, colonization, and reproduction processes of A. americanum on raspberry leaves, using light microscopy (bright field and fluorescence), confocal laser scanning microscopy, as well as scanning and transmission electron microscopy.Results and discussionOur findings provide the first microscopic evidence, in rust fungi, of the formation of two haustoria within a single host cell. Chloroplasts were observed in close association with the A. americanum haustorium, and underwent a series of alterations, that help to explain the drastic reduction in leaf gas exchange during late leaf rust infection. Although infected leaves produce defense substances, such as callose and phenolic compounds, raspberry leaves are unable to prevent successful colonization. The occurrence of cell collapses and necrosis, together with the ultrastructural alterations, likely contributes to the early defoliation observed in raspberry plants infected by A. americanum. This study provides novel insights into chloroplast-pathogen interactions, highlighting previously unrecognized aspects of chloroplast alterations during late leaf rust infection. Nevertheless, further investigations are required to deepen our understanding of this relationship in rust fungi as well as in other biotrophic pathogens.